PENGARUH KOMITE AUDIT, KOMISARIS INDEPENDEN, KEPEMILIKAN ASING DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN - May Wulandari (2020)
The research is a quantitative research in order to know the influence of audit committee, indepedendent commissioner, foreigh ownership and tenure audit towards financial statements integrity. 66 registered companies in Indonesia stock exchange (BEI) over a period of years 2016-2018 for a sample of this research, purposive sampling selected to determine the sample path analysis is analytical technique being used, software used is smartpls 3.2.2 with 5% level of significance, and as a metode is use structural equation model (SEM). Testing shows results (1) audit committee gave negative effect to financial statements integrity, (2) independent commissioner gave no effect to financial statements integrity, (3) foreigh ownership also gave no effect to financial statements integrity, (4) tenure audit gave positive effect to financial statements integrity.